2020
DOI: 10.1002/jmv.26239
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of dengue virus serotype 2 isolated from dengue fever outbreaks in eastern Uttar Pradesh and western Bihar, India

Abstract: Dengue (DEN) is the most common cause of mosquito‐borne endemic viral diseases in the tropical and subtropical countries. DEN outbreaks associated with multiple dengue virus (DV) serotypes have been regularly reported in different parts of India. This study was done during DEN outbreaks in 2015 to 2016 in UP and Bihar where DEN‐2 was found as the only prevalent serotype. DV‐2 was the only serotype amplified in serotype‐specific reverse‐transcription polymerase chain reaction from sera of 210 (65.21%) out of 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…[19]. Deval et al from Uttar Pradesh reported the DEN-2 serotype in the population[20]. These states are near Uttarakhand and many locals travel in this state regularly which gives support to the theory of serotypes difference due to the travellers from different parts of the country.…”
mentioning
confidence: 78%
“…[19]. Deval et al from Uttar Pradesh reported the DEN-2 serotype in the population[20]. These states are near Uttarakhand and many locals travel in this state regularly which gives support to the theory of serotypes difference due to the travellers from different parts of the country.…”
mentioning
confidence: 78%
“…Envelope protein (Protein Id: AWI48553.1) of Dengue virus 2 isolate NIV/GFU-DV-1615135 was downloaded from the protein database of NCBI. This strain was discovered in serum samples taken clinically confirmed the dengue fever in patients who visited from 2015 to 2016 in Gorakhnath Multispecialty Hospital, Gorakhpur (Deval et al 2021 ). E protein of DENV-2 was amplified from the virus in NIV, Gorakhpur, UP (Deval et al 2021 ).…”
Section: Methodsmentioning
confidence: 94%
“…This strain was discovered in serum samples taken clinically confirmed the dengue fever in patients who visited from 2015 to 2016 in Gorakhnath Multispecialty Hospital, Gorakhpur (Deval et al 2021 ). E protein of DENV-2 was amplified from the virus in NIV, Gorakhpur, UP (Deval et al 2021 ). E protein gene sequences from internationally scattered DENV-2 serotypes share 96–100% sequence similarity at the nucleotide level.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…India also continues to be a prominent location for dengue cases worldwide [ 2 , 5 ]. The epidemiology of dengue fever is undergoing significant developments, with more extensive and frequent outbreaks being recorded in urban and rural regions, attributable to each of the four serotypes in India [ 6 ]. Efforts are underway to improve dengue surveillance in India, but more seroepidemiological investigations are needed to estimate the disease burden accurately.…”
Section: Introductionmentioning
confidence: 99%